The relationship between principals instructional leadership and teachers efficacy in Xuzhou, China - Zhou, Entong; Abdul Aziz, Nor Azni (Human Resource Management Academic Research Society, 2023)
Teachers' efficacy is directly linked to how strongly they believe they can influence students' learning as well as how hard and persistent they work to make sure that happens. Some research suggests that principals' instructional leadership plays an important role in improving teacher efficacy, but empirical research in the Chinese context is still lacking. Therefore, the purpose of this study was to examine the relationship between principals’ instructional leadership and teachers’ efficacy in junior high schools in Xuzhou, China. This is a quantitative descriptive and correlational study using the Principal Instructional Management Rating Scale (PIMRS) constructed by Hallinger (1983) and the Teachers' Sense of Efficacy Scale (TSES) constructed by Megan Tschannen - Moran and Anita Woolfolk Hoy (2001). The study sample consisted of 180 teachers from four secondary schools in Xuzhou, China. Results were analyzed using frequencies, percentages, means, standard deviations, and Pearson correlation analysis. The study's main findings showed that the efficacy of teachers was significantly positively correlated with the instructional leadership of principals. This study also discovered that both principals' instructional leadership and teachers' efficacy were high. Therefore, this study supports other findings that the more principals practice instructional leadership behaviors, the more they will improve teacher efficacy.